2015
DOI: 10.1371/journal.pone.0135195
|View full text |Cite
|
Sign up to set email alerts
|

The Aspergillus fumigatus pkcAG579R Mutant Is Defective in the Activation of the Cell Wall Integrity Pathway but Is Dispensable for Virulence in a Neutropenic Mouse Infection Model

Abstract: Aspergillus fumigatus is an opportunistic human pathogen, which causes the life-threatening disease, invasive pulmonary aspergillosis. In fungi, cell wall homeostasis is controlled by the conserved Cell Wall Integrity (CWI) pathway. In A. fumigatus this signaling cascade is partially characterized, but the mechanisms by which it is activated are not fully elucidated. In this study we investigated the role of protein kinase C (PkcA) in this signaling cascade. Our results suggest that pkcA is an essential gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 106 publications
4
76
0
Order By: Relevance
“…1 × 10 7 conidia of A. niger N402 and ΔugmA strain were grown at 30 °C (200 rpm) in liquid CM during 18, 24 and 36 h or 24, 36 and 48 h for the wild‐type and Δ ugmA strains respectively. For protein extraction, 0.5 ml of lysis buffer added to the ground mycelia as described previously (Rocha et al, ). The supernatants were collected and the protein concentrations were determined according to the Lowry method modified by Hartree (Hartree, ).…”
Section: Methodsmentioning
confidence: 99%
“…1 × 10 7 conidia of A. niger N402 and ΔugmA strain were grown at 30 °C (200 rpm) in liquid CM during 18, 24 and 36 h or 24, 36 and 48 h for the wild‐type and Δ ugmA strains respectively. For protein extraction, 0.5 ml of lysis buffer added to the ground mycelia as described previously (Rocha et al, ). The supernatants were collected and the protein concentrations were determined according to the Lowry method modified by Hartree (Hartree, ).…”
Section: Methodsmentioning
confidence: 99%
“…fumigatus , AfPkcA, was recently studied for the first time (Rocha et al ., ). Attempts to delete the Af pkcA gene failed, which is in good agreement with several similar approaches in Aspergillus nidulans (Ichinomiya et al ., ; Ronen et al ., ; Teepe et al ., ; Rocha et al ., ). Rocha and colleagues therefore constructed an Af pkcA G579R mutant that carries a point mutation in the C1B regulatory domain of AfPkcA, a strategy that was previously successfully used to characterize the A .…”
Section: The Cell Wall Integrity Pathway a Conserved Signalling Cascadementioning
confidence: 97%
“…nidulans PkcA homologue (Hill et al ., ; Teepe et al ., ). The Af pkcA G579R mutant is hypersensitive towards chitin‐binding agents, heat, oxidative stress, azole and echinocandin antifungals (Rocha et al ., ). Similar to CaPkc1, AfPkcA and AnidPkcA were shown to influence CWI signalling.…”
Section: The Cell Wall Integrity Pathway a Conserved Signalling Cascadementioning
confidence: 97%
See 1 more Smart Citation
“…The A. fumigatus CWI pathway has already been characterized, and it is mainly composed of the PkcA-MpkA-Rlm1 module (36,(41)(42)(43)(44)(45). Recently, we demonstrated that the HOG MAPs SakA and MpkC are independently required to mount an adequate response to cell wall damage (29).…”
mentioning
confidence: 99%